ANALISIS TINGKAT KEMAMPUAN KEUANGAN DAERAH DALAM MENDUKUNG PELAKSANAAN OTONOMI DAERAH - Kamaroellah, R. Agoes (NUANSA: Jurnal Penelitian Ilmu Sosial dan Keagamaan Islam, 2017)
The purpose of this study was to determine the level of financial capability in Pamekasan in order to support the implementation of regional autonomy. This study took place in the Finance and Asset Management Agency Pamekasan regency. While the data used in this study is the financial data in the budget Finance and Asset Management Agency Regions 2011-2015 fiscal year. The data collection techniques is to study literature and documentationThis research method is descriptive quantitative, using financial ratios, ie the ratio of local financial independence, the ratio of the degree of decentralization, local financial dependency ratios. The results of the analysis conducted of data obtained as follows: Based on the ratio of local financial independence shown by the average ratios are 36.53%% remained between 25% - 50% are categorized as instructive meaningful relationship patterns Pamekasan governments ability to meet funding needed to perform the duties of Government, Development and Social Services community is still relatively low despite the years has increased and decreased. The degree of decentralization ratio only has an average of 6.4%. this means that the level of financial independence still low Pamekasan in implementing autonomy. Based on the area of financial dependency ratios averaging 19% are in scale interval, 10.01 to 20.00% this means that This means revenue (PAD) has a dependency large enough to cover immediate expenses and Pamekasan government still depends on the source financial receipts from central government and provincial transfers.